2020
DOI: 10.1186/s42774-020-00036-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rotor solidity on trailing edge noise from wind turbine blades

Abstract: Noise prediction from streamlined bodies such as wind turbine blades can be predicted accurately using CFD computations that use spatio-temporal turbulence models at the expense of high computational power. In this work, empirical methods proposed from BPM, Grosveld and Lowson are used to compute numerically to analyse the influence of rotor solidity factor on broadband trailing edge noise from a 2 MW horizontal axis wind turbine with a blade length of 37 m. Inputs to acoustic solver are the velocity vector fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This plays critical role in turbines structural response and estimation of fatigue and extreme loads behavior in turbine design (Shigeo and Metwally, 2018) For instance, fatigue study by Shigeo and Metwally (2018) showed that a small increase in turbulence intensity level, from 1% to 10%, a significant reduction of time to failure of wind turbine components were observed. Particularly blades of wind turbine are more sensitive to turbu- lence and subjected to higher fluctuating loads (Bhargava et al, 2020;Nukala and Maddula, 2020;. Further, the damage equivalent loads (DEL) predicted by Von Karman and Kaimal turbulence spectra in the study were found to agree within 5% of peak values for different turbulence intensities.…”
Section: Resultsmentioning
confidence: 64%
“…This plays critical role in turbines structural response and estimation of fatigue and extreme loads behavior in turbine design (Shigeo and Metwally, 2018) For instance, fatigue study by Shigeo and Metwally (2018) showed that a small increase in turbulence intensity level, from 1% to 10%, a significant reduction of time to failure of wind turbine components were observed. Particularly blades of wind turbine are more sensitive to turbu- lence and subjected to higher fluctuating loads (Bhargava et al, 2020;Nukala and Maddula, 2020;. Further, the damage equivalent loads (DEL) predicted by Von Karman and Kaimal turbulence spectra in the study were found to agree within 5% of peak values for different turbulence intensities.…”
Section: Resultsmentioning
confidence: 64%
“…The thin shear layer emanating from the slat cusp and its subsequent reattachment upstream of the slat trailing edge produces broad-band noise. Finally, tonal noise produces narrow band peaks whose amplitudes are function of characteristic trailing edge geometry, angle of attack, Reynolds number, Strouhal number and state of the boundary layer flow (Nukala & Maddula, 2020). Further, a tonal noise peak is quite often associated with vortex shedding behind a slat trailing edge with a finite thickness and produced due to stall separation inside the slat cove region.…”
Section: Noise Radiation From High Lift Systemsmentioning
confidence: 99%